Enhanced pool boiling performance of a porous honeycomb copper surface with radial diameter gradient. (August 2020) - Mo, Dong-Chuan; Yang, Shuo; Luo, Jia-Li; Wang, Ya-Qiao; Lyu, Shu-Shen
Highlights: Porous honeycomb copper surface with radial diameter gradient was fabricated. Has superior heat transfer performance than samples with uniform pore diameters. The heat transfer coefficient can be as high as 16.1 Wcm –2 K –1 . The diameter gradient lead to larger K / R eff, lower Δ T ONB and faster bubble growth. Abstract: Boiling heat transfer (BHT) is widely used in industry and in our daily lives, and it can be enhanced by micro/nano structures. Previously, porous honeycomb copper surfaces have been proven to significantly enhance BHT performance, but how a radial pore diameter gradient affects BHT is still unknown. In this paper, two porous honeycomb copper surfaces with uniform pore diameters of 60 and 120 μm, respectively (named Sample#U1 and Sample#U2), were prepared using the electrochemical deposition method. On this basis, a porous honeycomb surface with a radial diameter gradient was prepared by infusing liquid onto the reaction surface during the deposition process. The range of pore diameters from the center to the edge was 60–120 μm (named Sample#G1). Pool boiling experiment results showed that the sample with the radial diameter gradient had superior heat transfer performance. Sample#G1, with the smallest pores at the center and largest pores at the edge, had a maximum nucleate BHT coefficient h MNB of 16.1 Wcm –2 K –1, which was about 1.4 times that of Sample#U2, 1.5 times that of Sample#U1, and 3.5 times that of a pure copper surface. It was assumed that surfaces with a radial diameter gradient had a superior rewetting ability, and this was confirmed in a capillary wicking experiment. The K/Reff of the sample with the radial diameter gradient was larger than those of the samples with uniform diameter, which indicated that a radial diameter gradient surface could quickly accelerate the replenishment of water in pool boiling. A porous structure provides pores and cavities, which was benefit for activate bubble nucleation under a low superheat. Sampe#G1 had the lowest Δ TONB . The bubble dynamics also proved that the sample with the radial diameter gradient had a faster bubble growth speed than those with a uniform diameter, resulting in faster heat removal.